Knowledge, attitudes and practices of parents/guardians of children with disabilities on abuse of children with disabilities, in the Willowvale area, Eastern Cape Province, South Africa - Wogqoyi, Mirriam Ntombesoka (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.